1991
DOI: 10.3109/15513819109065471
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Extragonadal Teratoma: Case Report of an Immature Teratoma Occurring in a Prenatal Brain

Abstract: We describe a massive congenital intracranial teratoma (MCIT), which had a normal chromosome banding pattern 46,XY karyotype and a normal diploid DNA histogram, and which produced a variety of carcinoembryonic antigens. The volume density of primitive neural components (primitive neural tubes, small undifferentiated neuroepithelial cells, immature glial fibers and pigment cell components without neurofibrillar differentiation) was estimated to be 45%. We discuss the histogenesis, pathobiology and cell cycle ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Extragonadal teratomas are thought to arise from primordial germ cells or early embryonic cells while gonadal teratomas arise from germ cells in which parthenogenesis has occurred [3]. Wagner et al [4] demonstrated that extragonadal teratomas arise from totipotential cells with a diploid chromosome.…”
Section: Theories Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Extragonadal teratomas are thought to arise from primordial germ cells or early embryonic cells while gonadal teratomas arise from germ cells in which parthenogenesis has occurred [3]. Wagner et al [4] demonstrated that extragonadal teratomas arise from totipotential cells with a diploid chromosome.…”
Section: Theories Of Originmentioning
confidence: 99%
“…Immature teratomas contain at least 10% undifferentiated tissue and are devoid of malignant components or metastases. Immature teratomas are most commonly of neural origin [3].…”
Section: Classification Of Teratomasmentioning
confidence: 99%
“…The presence of teratomas distant from this migration route is more difficult to explain. There is evidence suggesting that extragonadal teratomas occurring at these distant sites may occur through one or more different pathways 19 . The embryonal cell theory postulates that pluripontential blastomeres, segregated from the primitive streak during early embryonic development, escape the influence of the primary organiser 1,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The term ''immature teratoma'' has been used to describe a neoplasm that not only contains elements derived from the three germ cell layers but also contains rests of unrecognizable, poorly differentiated tissue, which is generally considered to be of neural origin. 28 If the teratoma is presumed to have arisen in the gonad from premeiotic diploid germ cells, postmeiotic haploid germ cells, or cells derived from extraembryonic components such as the yolk sac, the term ''germ cell tumor'' may be applied. 28,32 Teratomas may be benign (as is commonly the case in domestic species) or malignant, with metastasis of one or more components to distant sites (seen with a higher incidence in laboratory rodents and humans).…”
mentioning
confidence: 99%
“…28,32 Gonadal teratomas are presumed to develop from parthenogenetic development of sequestered haploid postmeiotic germ cells or diploid premeiotic germ cells in the gonad. The exact precursor cell is still unknown.…”
mentioning
confidence: 99%